Major transcripts containing B1 and B2 repetitive sequences in cytoplasmic poly(A)+RNA from mouse tissues - Ryskov, A P; Ivanov, P L; Tokarskaya, O N; Kramerov, D A; Grigoryan, M S; Georgiev, G P (FEBS letters, 1985)
The cytoplasmic poly(A)+RNAs containing ubiquitous B1 and B2 repeats of the mouse genome in normal tissues and tumors have been studied. Only one strand of the repeats is represented in cytoplasmic RNA in all the cases. Some tumor cells were found to be enriched in 1.4 kb B1+mRNA, 1.6 kb B2+mRNA and small (0.2-04 kb) B1+ and B2+ poly(A)+RNAs. On the other hand, mouse liver and kidney contained high amounts of 2 kb B2+mRNA. Its content increased noticeably in the regenerating liver, but in hepatoma it dropped to a zero level. Thus, the switching on (or off) of B1- and B2-containing mRNAs occurred noncoordinately. At the same time, the activation of the synthesis of small B2+RNA and small B1+RNA was simultaneous.